Investigation of an integrative transverse-flux linear compressor. Issue 6 (2nd November 2015) - Lu, Qinfen; Yao, Yihua; Ye, Yunyue
Abstract : Purpose: – The purpose of this paper is propose a novel integrative transverse-flux linear compressor (TFLC), which integrates compressor into a single-phase transverse-flux linear oscillating actuator with moving magnet. Its main merit is having similar lamination as rotate motor which is easy to be stacked. Design/methodology/approach: – The simple lumped circuit model accounting for magnetic saturation, armature reaction and axial fringing effect is proposed. Based on this model, the magnetic field in air gap is calculated, and then the optimal PM height, PM length, split ratio and pole number are found. The predicted thrust force, stroke and system resonant frequency at no load are validated by prototype measurement. The relation of system resonant frequency and load are also measured. Findings: – In this novel TFLC, the optimal split ratio is in area of 0.54∼0.56 and pole number is 6. For designed stroke 10 mm, suitable PM height and length are 3 mm and 63 mm, respectively. By measurement, the predicted thrust force, stroke and system resonant frequency at no load are validated. The measurement also shows that the system resonant frequency can be improved from 30 Hz of no load to 39 Hz at 0.7 Mpa air load. Originality/value: – The novel TFLC has excellent driving performance and simple structure for maintenance. It can produce enough pressure to meet the requirement of refrigerator, so it is a strong candidate for refrigerating apparatus.